Quench dynamics in MgB2 Rutherford cables. (9th March 2018) - Cubero, A; Navarro, R; Kováč, P; Kopera, L; Rindfleisch, M; Martínez, E
Abstract: The generation and propagation of quench induced by a local heat disturbance or by overcurrents in MgB2 Rutherford cables have been studied experimentally. The analysed cable is composed of 12 strands of monocore MgB2 /Nb/Cu10Ni wire and has a transposition length of about 27 mm. Measurements of intra- and inter-strand voltages have been performed to analyse the superconducting-to-normal transition behaviour of these cables during quench. In case of external hot-spots, two different time-dynamic regimes have been observed, a slow stage for the formation of the minimum propagation zone (MPZ), and a fast dynamics once the quench is triggered and propagates to the rest of the cable. Significant local variations of the quench propagation velocity across the strands around the MPZ have been observed, but with average quench propagation velocities closely correlated with the predictions given by one-dimensional-geometry models. For quench induced by overcurrents (i.e. with applied currents higher than the critical current) the nucleation of many normal zones distributed within the cable, which overlap during quench propagation, gives a distinctive and faster quench dynamics.